(untitled) (The Peerian Journal, 2024)
Digital marketing is one of the modern concepts that have emerged recently as a result of the information revolution and technological development that has swept the world. The importance of the study stems from the role played by modern marketing trends (digital marketing) in transforming tourism activity into a competitive arena, as it works to connect individuals to each other through technology, In addition, the study aims to highlight the role of digital marketing in promoting tourism activities in general and tourism services in particular, considering digital marketing the distinguishing factor in tourist attractions, which has become at present a definite and indispensable necessity in activities Tourist